THE CONCEPT OF NATURE IN THE WORKS OF AMERICAN TRANSCENDENTALIST HENRY DAVID THOREAU - Liebiedieva, Hanna (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2024)
B a c k g r o u n d . This article reveals the understanding of the concept of nature in the works of the American philosopher Henry David Thoreau. Henry David Thoreau is an American philosopher, poet, essayist, naturalist and political activist. Together with Ralph Waldo Emerson, his friend and mentor, he is considered one of the founders of the transcendentalist movement. Transcendentalism was a powerful movement of American philosophy of the 19th century. It was characterized by focusing on the problem of human self-knowledge, human's returning to own essence, living in harmony with nature, as well as criticism of modern society and active abolitionism. M e t h o d s . The article uses both general scientific methods and special methods, such as – the method of historical-philosophical reconstruction, which made it possible to reproduce the ideas of the American thinker, the hermeneutic method – for explaining individual positions of the philosopher. In addition, literary-critical methods were used, for the possibility of using various primary sources, and systematic method – to identify a systematized structure in the philosophical work of H. D. Thoreau. R e s u l t s . One of the main features of transcendentalism is a special interest in reflection on nature and a special approach to it. Thus, the concept of nature is present in most of H. D. Thoreau's works, and it is the central topic of his philosophical searches. The concept of nature in his works appears in different contexts, acquires different meanings. Thus, H. D. Thoreau talks about nature in the context of nature, in the context of poetic creativity, in his philosophical searches, in his vision of man and in his argumentation of his own political position. However, the different meanings that H. D. Thoreau attaches to the concept of nature do not contradict each other, but, on the contrary, complement and clarify his understanding of nature. C o n c l u s i o n s . This article proposes to consider the use of the concept of nature by H. D. Thoreau in the following aspects: Nature and Peculiarities of nature as a subject of scientific knowledge. Nature and The relationship between nature and culture through the relationship between "the wild" and society. Nature and From naturalism to humanism. Nature as an inner essence of man and solitude with nature as a return to this essence.